2003
DOI: 10.1525/sop.2003.46.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Family Strain, Gender, and Delinquency

Abstract: In the last decade, Robert Agnew's general strain theory (GST) of delinquency has received considerable empirical attention, with most studies yielding favorable evidence. One aspect of GST neglected by researchers, however, concerns its ability to explain why certain demographic variables are related to delinquency. This article reports such a test of GST with respect to the gender-delinquency relationship in particular—one of the strongest relationships in delinquency research. The focus is on family-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
180
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(200 citation statements)
references
References 66 publications
(95 reference statements)
17
180
3
Order By: Relevance
“…Many of the main concepts pertaining to GST have been thoroughly tested, most specifically, the direct relationship between strain and delinquency. Overall, the research has consistently found a positive relationship between strain and delinquent behavior (e.g., Agnew, 2002;Agnew et al, 2002;Agnew & White, 1992;Aseltine et al, 2000;Brezina, Piquero, & Mazerolle, 2001;Hay, 2003;Paternoster & Mazerolle, 1994). Indeed, in almost every published test of GST, at least one measure of strain has been found to positively influence delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 96%
See 4 more Smart Citations
“…Many of the main concepts pertaining to GST have been thoroughly tested, most specifically, the direct relationship between strain and delinquency. Overall, the research has consistently found a positive relationship between strain and delinquent behavior (e.g., Agnew, 2002;Agnew et al, 2002;Agnew & White, 1992;Aseltine et al, 2000;Brezina, Piquero, & Mazerolle, 2001;Hay, 2003;Paternoster & Mazerolle, 1994). Indeed, in almost every published test of GST, at least one measure of strain has been found to positively influence delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 96%
“…Research has failed to find consistent support for the conditioning hypothesis of GST in explaining delinquency (e.g., Agnew & White, 1992;Aseltine et al, 2000;Brezina, 1996;Hay, 2003;Hoffmann & Miller, 1998;Mazerolle & Maahs, 2000;Paternoster & Mazerolle, 1994;Piquero & Sealock, 2000;Robbers, 2004). A number of possible conditioning factors have been examined including social support (e.g., Robbers, 2004), self-esteem (e.g., Hoffmann & Miller, 1998), depression (e.g., Piquero & Sealock, 2000), anger (e.g., Hay, 2003), delinquent peer exposure (e.g., Piquero & Sealock, 2004), religiosity (e.g., Jang & Johnson, 2005), and others.…”
Section: Empirical Research On Gstmentioning
confidence: 99%
See 3 more Smart Citations